Answer:
(6x - 7y)(6x + 7y)
Step-by-step explanation:
36x² - 49y² ← is a difference of squares and factors in general as
a² - b² = (a - b)(a + b) , then
36x² - 49y²
= (6x)² - (7y)²
= (6x - 7y)(6x + 7y)
Hope it will help u........
The diameter is 10 so it would be pi•radius squared 3.14•52sq or 3.14•10•2=78.54 the base of the circle is 78.54
Answer:
D
Step-by-step explanation:
We can see in the graph f(x) that the x intercept is
.
In the table of g(x), we can see that the x intercept is
.
Since
, the x intercept of the graph f(x) is greater than the x intercept of graph g(x).
Use product rule: x^a x^b = x^a + b
a^5 + 4 - 2
Simplify 5 + 4 - 2 to 7
Answer: a^7